(untitled) (Revista de Ciências Agroveterinárias, 2024)
Fungal pathogens exist obviously in environment; therefore, animals may act as a source of infection to human. Pichia kudriavzevii is ubiquitous fungus of lastly great attention due to its potential use in biotechnology and processing of food, and controversial safety. This study aims to determining the prevalence rate of subclinical mastitis in lactating cows, and demonstration the presence of Pichia kudriavzevii in milk of positively mastitic cows using the molecular phylogeny. Totally, 400 adult lactating cows were subjected for collection an approximately 50 ml of fresh milk that tested initially with the California Mastitis Test (CMT); and then, positive samples have tested molecularly using conventional polymerase chain reaction (PCR). Some molecularly positive samples were analyzed phylogenetically for confirming of local isolates in the National Centre for Biotechnology Information (NCBI). Overall, 54.25% cases were positively reacted by CMT. According to score of positivity, 83.87%, 11.98% and 4.15% were showed weak, distinct, and strong positive infections, respectively. Targeting the ITS region, 28.11% of samples were reacted positively to P. kudriavzevii at 278 bp. Phylogenetic analysis of eight local P. kudriavzevii isolates showed the nucleotide alignment similarity and substitutions. Phylogenetic tree analysis revealed that the local P. kudriavzevii isolates were showed a genetic identity to the NCI-BLAST P. kudriavzevii Mexico isolates (KY646192.1) at total genetic changes ranged 0.0035-0.005%. In conclusion, this represents first molecular phylogenic study in Iraq implicates the presence of P. kudriavzevii in subclinical mastitic cows. Nationwide surveys are useful in monitoring udder health, studying the impact of structural changes, and estimating the factor(s) contribute in incidence of disease and the role of different fungi in it.